Behavior of RC Eccentric Corner Beam-Column Joint under Cyclic Loading: An Experimental Work - Ali Basha; Sabry Fayed (Salehan Institute of Higher Education, 2019)
The present research investigates experimentally the behavior of the reinforced concrete BCJ joint under quasi-static cyclic loads for different mount of the shear reinforcement. The specimen consisted of two columns and two beams; one is a free end and the other is a fixed end. The shear reinforcement of the joint was 1Ø6 mm, 2Ø6 mm, and 3Ø6 mm. Three specimens were tested under quasi-static cyclic loading up to failure. The cracking loads, ultimate loads, deflection of the free end of the loaded beam, crack patterns and failure modes for BCJ were recorded and analyzed at each cycle. Also energy dissipation and stiffness degradation of all specimens were discussed. The experimental result indicates that the increase in the amount of the stirrups of the joint transmitted the main failure into the column far away from the joint. The increase in the amount of joint stirrups enhanced the joint capacity. The stirrups are most effective in is the middle third part of the BCJ than others two parts.